Risk Evaluation for the Formation of Gastroduodenal Erosion and Ulceration Induced by Meloxicam in Patients with Seropositive and Seronegative Rheumatoid Arthritis - R. A. Pavlyukov; M. R. Konorev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. In this paper, the authors set out toascertain the prognostic value of the rheumatoid factor for the formation of gastroduodenal erosions and ulcers in patients with rheumatoid arthritis taking non-steroidal anti-inflammatory drugs (meloxicam).Materials and methods. A prospective, randomized study of 138 patients with rheumatoid arthritis taking methotrexate (12.5 mg per week) and meloxicam — nonsteroidal anti-inflammatory drug — (15 mg per day) was conducted. The formation of gastroduodenal erosions and ulcers was recorded for 4–8 years during esophagogastroduo-denoscopy (at study entry, following three months, then once a year). The groups of seropositive and seronegative patients comprised 69 people each.Results. During the period of patient monitoring, significant differences were found (P < 0.01) in the frequency of the formation of gastric and duodenal erosions and ulcers in patients with seropositive (79.7 %; 95 % CI: 70.2–89.2 %) and seronegative (4.4 %; 95 % CI: 0.01–9.2 %) rheumatoid arthritis (τ = 0.763; P < 0.01), taking meloxicam. In the course of monitoring patients (for 4–8 years) with rheumatoid arthritis who took meloxicam, the authors established high rates of the prognostic (rheumatoid) factor for predicting the formation of gastric and duodenal erosions and ulcers: forecast sensitivity — 94.8 %, forecast specificity — 82.5 %, the proportion of correct forecasts — 87.7 %.Conclusions. The rheumatoid factor is found to be a significant (P < 0.01) risk factor for gastroduodenal erosions and ulcers in patients with rheumatoid arthritis, who take non-steroidal anti-inflammatory drugs (meloxicam).